Chromium Content in the Human Hip Joint Tissues - Barbara Brodziak-Dopierala Jerzy Kwapulifiski Krzysztof Sobczyk Danuta Wiechula (Biomedical and environmental sciences, 2015)
Objective Chromium has many important functions in the human body. For the osseous tissue, its role has not been clearly defined. This study was aimed at determining chromium content in hip joint tissues. Methods A total of 91 hip joint samples were taken in this study, including 66 from females and 25 from males. The sample tissues were separated according to their anatomical parts. The chromium content was determined by the AAS method. The statistical analysis was performed with U Mann-Whitney＇s non-parametric test, P〈0.05. Results The overall chromium content in tissues of the hip joint in the study subjects was as follows： 5.73 μg/g in the articular cartilage, 5.33 μ/g in the cortical bone, 27.86 μ/g in the cancellous bone, 5.95 μg/8 in the fragment of the cancellous bone from the intertrochanteric region, and 2.28 μ/g in the joint capsule. The chromium contents were observed in 2 group patients, it was 7.04 μ/g in people with osteoarthritis and 22.59 μ/g in people with fractures. Conclusion The observed chromium content was highest in the cancellous bone and the lowest in the joint capsule. Chromium content was significantly different between the people with hip joint osteoarthritis and the people with femoral neck fractures.